SEMIOTIKA PADA MICROLIBRARY BIMA BANDUNG - Noorzanah, R Aj. Dewi Sekar; Laksemi, Sangayu Ketut; Hutama, Krishna (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2022)
Abstract Semiotics at the Bima Bandung Microlibrary. The study of semiotics in building has not been done much. Therefore, I conduct a study of the message behind architectural design in the context of semiotic theory by taking the case of the Bima Bandung microlibrary. The purpose of this study is to understand the denotative and connotative messages in the Bima microlibrary. The study refers to the case study method of qualitative research. In the microlibrary Bima conveys a message of 1)war against low literacy levels, 2) is an example of improving public spaces, 3) giving messages of environmentally conscious design, 4)the use of used plastic buckets is arranged to form the word "Books are the Window of the World". The denotative meanings of Bima's microlibrary are: location in a densely populated residential area, the building is in the form of a box, supported by a steel structure, the color of the building is black for the structure, the walls and windows are white. The connotative meaning is that the presence of the building does not interfere with existing open space facilities. The shape of the building becomes a symbol of progressive, inviting people to advance through reading books. The window material creates a dramatic effect, giving the impression that the building cares about environmental issues. Keywords: microlibray, semiotics, building, denotative, connotative. Abstrak Semiotika pada Microlibrary Bima Bandung. Kajian semiotika pada bangunan masih belum banyak dilakukan. Oleh karena itu kami melakukan kajian tentang pesan dibalik karya bangunan dalam konteks teori semiotika dengan mengambil kasus microlibrary Bima Bandung. Tujuan penelitian ini adalah mencoba memahami pesan denotatif dan konotatif pada microlibrary Bima. Tulisan mengacu pada metode studi kasus penelitian kualitatif. Pada microlibrary Bima menyampaikan pesan tentang 1) perang terhadap rendahnya tingkat literasi, 2) merupakan contoh memperbaiki ruang publik, 3) memberi pesan rancangan yang sadar terhadap lingkungan, 4)penggunaan material bekas ember plastik ditata membentuk kata “Buku adalah Jendela Dunia”. Makna denotatif microlibrary Bima yaitu: lokasi di kawasan pemukiman padat, bangunan berbentuk balok, yang ditopang struktur baja, warna bangunan hitam untuk struktur, dinding dan jendela berwarna putih. Makna konotatif yaitu kehadiran bangunan tidak mengganggu fasilitas ruang terbuka yang ada sebelumnya. Bentuk bangunan menjadi simbol kemajuan, mengajak masyarakat maju melalui membaca buku. Material jendela menimbulkan efek dramatis, memberi kesan bahwa bangunan peduli terhadap isu lingkungan. Kata kunci: microlibray, semiotika, bangunan, denotatif, konotatif.